Insects on the Prairie - Valerie Wright (Symphony in the Flint Hills, 2013)
Insects make up about ninety percent of the animals on earth. They live above and below ground and are found flying at high altitudes or living in water, soil, plant, or animal tissue - literally filling every niche possible for life.
Keywords: grasshoppers; insects; bugs; pests; nature; native; natural; species; reproduction; animals; evolution; evolved; toxins; toxic; plants; morphology; parts; cicada; Prairie Cicada; Malampsalta calliope; K-State; Homoptera; Insect Zoo; Kansas State University